Konsep Kritik Matan: Sejarah, Tujuan, Manfaat, dan Langkah – Langkah Penelitian Matan Hadis - Jailuddin, Syuaib (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The criticism of hadith texts is a discipline in the study of hadith that aims to test the validity and authenticity of hadith texts, both in terms of sanad and matan. The concept of this criticism is rooted in the term "naqd," which means to examine, distinguish, and separate between the authentic and the flawed. The tradition of hadith criticism has existed since the time of the Prophet Muhammad, with various motives such as clarification and confirmation, and developed further during the time of the Companions and the Muhaddisin period. The criticism of matan serves to maintain the purity of Islamic teachings, prevent errors in understanding hadith, and face the challenges of forgery of hadith that have emerged throughout history. The method of criticism of matan hadith involves steps such as collecting hadiths with similar themes, testing the conformity of matan with the Qur'an and other hadiths, analyzing the language and structure of the text, and considering the historical context (asbab al-wurud). In addition, this approach also includes efforts to harmonize the content of hadiths that appear contradictory through the principles of mukhtalif al-hadith. This study emphasizes the importance of matan criticism in protecting the integrity of Islamic teachings from distortion and ensuring the correct understanding of the words of the Prophet Muhammad SAW. Thus, matan criticism of hadith is not only a scientific endeavor, but also a responsibility to maintain the continuity and authenticity of religious teachings.